Peta Sosial Ekonomi Umat Islam (Ekonomi Dalam Pembangunan dan Pengembangan Masyarakat Islam) - Dinny Rahmayani Zebua; Riswan Rambe (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This community development approach seeks to promote economic development at the local/regional level. Although such an approach is likely to involve community development and can be linked to empowerment activities in community action programs that focus on upgrading local infrastructure and promoting local economic development projects. This is a key theme related to community development programs by taking into account the economic principles of Muslims. Community development is known as community development. According to the Director General of Development, it is essentially a continuous dynamic process for the community to realize the desire and expectation of a more prosperous life with a strategy to avoid the possibility of being cornered by the community as the guarantor for access to regional or national development. Community Development becomes a kind of spirit in a development paradigm that is no longer delivered where it has been planned by the highest party or follows western patterns, but becomes a development that is people centered in color. With the development of ideas in the theory of dependency (relationships of dependency, there are dominant parties and dependent parties) who want to be independent and contextual in improving people's welfare. More than that, the bottom-up principle becomes a promising belief on the basis of the failure of various countries to improve the welfare of their people.